Mass suicides on Saipan and Tinian, 1944 : an examination of the civilian deaths in historical context - Astroth, Alexander, 1992- (McFarland & Company, Inc., Publishers, 2019)
"When the Americans invaded the Japanese-controlled islands of Saipan and Tinian in 1944, civilians and combatants committed mass suicide to avoid being captured. This book draws on United States National Archives documents and photographs, as well as veteran and survivor testimonies, to provide readers with a better understanding of what happened on the two islands and why"--